Mecanismos alternativos de resolução de conflitos: a solução para a garantia do acesso à justiça - Gil, Alan Junqueira (2020)
The present dissertation has as its main objective the analysis of alternative conflict resolution mechanisms of the state jurisdictional protection (pre and post judicialization of the demands) as a solution to the slowness and inefficiency of the Brazilian judicial system in the solution of the demands. Scientific research used the hypothetical-deductive method of approach, whose problem is the inability of the Brazilian judiciary system to meet all disputed cases in order to guarantee real access to justice. Moreover, the historical, comparative and observational methods of procedure were also used in the research, since the focus is on the investigation, comparison and observation of past data and events to verify their influence on Brazilian society and its future perspectives. In addition, there was the use of qualitative, descriptive-exploratory, bibliographic and documentary research techniques to solve this problem. The hypothesis that will be confirmed in the final considerations is that alternative conflict resolution mechanisms meet the decongesting objectives of the judiciary, ensuring access to justice. It is concluded that the speedy and effective resolution of disputes can and should be carried out by methods other than state jurisdictional protection, however, it is necessary to establish a culture of social pacification, in which citizens are aware that access Justice does not depend on the decision of the Judge State.